2021
DOI: 10.3748/wjg.v27.i24.3630
|View full text |Cite
|
Sign up to set email alerts
|

High rate of complete histopathological response in hepatocellular carcinoma patients after combined transarterial chemoembolization and stereotactic body radiation therapy

Abstract: BACKGROUND Liver transplantation (LT) presents a curative treatment option in patients with early stage hepatocellular carcinoma (HCC) who are not eligible for resection or ablation therapy. Due to a risk of up 30% for waitlist drop-out upon tumor progression, bridging therapies are used to halt tumor growth. Transarterial chemoembolization (TACE) and less commonly stereotactic body radiation therapy (SBRT) or a combination of TACE and SBRT, are used as bridging therapies in LT. However, it remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The safety and effectiveness of the combination of TACE and SBRT has also been evaluated in the bridging scenario. The rate of complete necrosis in liver specimens was higher in the combination therapy group (8 out of 9 patients, 89%) with respect to the TACE (0 of 14 patients, 0%) and SBRT (1 of 4 patients, 25%) groups [ 89 ]. The low sample size and retrospective nature of the study do not allow definitive conclusions to be drawn about the role of this combination therapy, which needs to be investigated in further studies.…”
Section: Treatments For Bridging and Downstagingmentioning
confidence: 99%
“…The safety and effectiveness of the combination of TACE and SBRT has also been evaluated in the bridging scenario. The rate of complete necrosis in liver specimens was higher in the combination therapy group (8 out of 9 patients, 89%) with respect to the TACE (0 of 14 patients, 0%) and SBRT (1 of 4 patients, 25%) groups [ 89 ]. The low sample size and retrospective nature of the study do not allow definitive conclusions to be drawn about the role of this combination therapy, which needs to be investigated in further studies.…”
Section: Treatments For Bridging and Downstagingmentioning
confidence: 99%
“…TACE is the most widely used method. In SIRT, yttrium-90 microspheres are infused intra-arterially for radioembolization [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, it was concluded that SBRT is a good option as an alternative to conventional therapies [ 60 ]. Bauer et al published a multi-center study in 2021 [ 61 ]. They analyzed the microscopic response to TACE and SBRT combined therapy in comparison to TACE or SBRT alone for the treatment of HCC.…”
Section: Bridging Therapies In Advanced Stage According To Bclcmentioning
confidence: 99%
“…Nevertheless, TACE or SBRT as a single approach presented lower rates of histopathologic CR (0% and 25%, respectively; p < 0.001). These data revealed that combined TACE and SBRT improve the outcomes in bridging to OLT [ 61 ].…”
Section: Bridging Therapies In Advanced Stage According To Bclcmentioning
confidence: 99%